La rêverie in Psicoanalisi e la teoria del Sé in Gestalt: un lavoro di integrazione attraverso lo studio delle esperienze immaginative in psicoterapia - 1 Marco Architravo, 2 Daniela Cantone (Phenomena Journal)
The imaginative world, as emerges from the relational dynamic, appears to be the connecting element between thoughts and emotions, and constitutes a factor of great communicative efficacy for therapist and patient. Bion’s work on the concept of rêverie, on the alpha function analysis and on the role of beta elements, shows common standpoints with the Theory of the Self developed by Pearls. This work intends to bring into sharper focus the role of the Imagination as unconscious communication instrument, by trying to classify the imaginative experiences with which the therapist is confronted throughout the course of the relationship with the patient. Type 1 images are identified that originate from the memory register of the therapist and Type 2 images originated instead from a new construction, or more similar to the dreamlike imaginative productioTwo different ways will be described, through which the therapists mind satisfies its own needs of imagining what comes from the experience told by the patient. These two different representations will be treated from three different points of view: Bion’s psychoanalytic work, Gestalt’s psychotherapy and Pearl’s work. By putting together different models of the countertransference function, this work makes an attempt to describe how both approaches address this specific function of the mind, even if through different languages. The work emphasizes nevertheless show the Imagination can be used in the clinical practice as a connecting instrument between the two actors of the therapeutical relationship.